2010
DOI: 10.4314/jasem.v14i3.61473
|View full text |Cite
|
Sign up to set email alerts
|

Physico-chemical characteristics and Heavy metal levels in Drinking Water sources in Sokoto metropolis in North-western Nigeria

Abstract: ABSTRAC:This study investigated the physico-chemical characteristics of drinking waters collected from tap, well and sachet in Sokoto metropolis in North Western Nigeria. Conductivity and pH values were determined by standard methods while elemental composition was analysed using X-ray Fluorescence spectroscopy. Majority of the water samples had neutral pH (6.80 -7.20) few were slightly alkaline and one was acidic. Tap water samples had similar conductivity values (180 -190µS/m), sachet water samples had condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…Urinary antimony, beryllium, bismuth, silver, thorium and vanadium were also very low with a high percentage of nondetects. Drinking water concentrations were also low with concentrations generally below available guidelines or concentrations reported in other studies (ATSDR, 2004a,b,c;ATSDR, 2012;Raji et al, 2010).…”
Section: Discussionmentioning
confidence: 86%
“…Urinary antimony, beryllium, bismuth, silver, thorium and vanadium were also very low with a high percentage of nondetects. Drinking water concentrations were also low with concentrations generally below available guidelines or concentrations reported in other studies (ATSDR, 2004a,b,c;ATSDR, 2012;Raji et al, 2010).…”
Section: Discussionmentioning
confidence: 86%
“…Lead (Pb) was also found at high level in this study. Raji et al (2010) reported the presence of heavy metals and other elements in relatively high concentrations in the drinking waters in the same geographical zone. In another work by Raji et al (2015), it was found that water from River Sokoto contained Hg, Cd and Ag and the bottom soil sediments at two sampling points contained Pb at concentrations above WHO's permissible limit.…”
Section: Resultsmentioning
confidence: 94%
“…Ca levels are mostly not regulated. However, sometimes these values are much higher in drinking water, and in extreme situations can reach as high as 25 mg/l Fe (49). All of these scenarios were within concentrations we investigated.…”
Section: Discussionmentioning
confidence: 52%
“…iii) The coordination of aluminium, Ca, Fe, Mg, Mn, Na with TFs has been reported by a number of studies (33,(41)(42)(43)(44)(45)(46)(47)(48)(49). However, O'Coinceanainn et al (22) and Tanaka et al (35) suggested that the reaction between TFs involves the formation of a metal complex, followed by subsequent decomposition or formation of the non-metallic intermediates that generate high molecular weight oxidized TF products.…”
Section: Discussionmentioning
confidence: 98%